OJS Release History: Some major and minor releases - Stevens, Amanda (PKP Barcelona 2019 Workshop, 2019)
OJS 1.0 - 2001 OJS 2.0 - 2005 OJS 2.4.8 - February 2016 OJS 3.0 - August 2016 OJS 3.1 - October 2017 OJS 3.1.2 - March 2019 OJS 3.1.2-1 - October 2019 OJS 3.2 - January 2020